Public health implications of multiple disaster exposures - Claire Leppold, PhD; Lisa Gibbs, ProfPhD; Karen Block, PhD; Lennart Reifels, PhD; Phoebe Quinn, MPH (Elsevier, 2022)
Summary: Disasters are an important public health issue; however, there is scarce evidence to date on what happens when communities and populations experience more than one disaster. This scoping review identifies literature on the effects of multiple disasters published until Aug 2, 2021, 1425 articles were identified, of which 150 articles were included. We analysed direct and indirect public health implications of multiple disasters. Our analysis suggests that exposure to multiple disasters can affect mental health, physical health, and wellbeing, with some evidence that the potential risks of multiple disaster exposure exceed those of single disaster exposure. We also identified indirect public health implications of multiple disaster exposure, related to changes in health-care facilities, changes in public risk perception, and governmental responses to multiple disasters. We present findings on community recovery and methodological challenges to the study of multiple disasters, and directions for future research.